A short history of Western performance space - Wiles, David (Cambridge University Press, 2003)
This innovative book provides a historical account of performance space within the theatrical traditions of western Europe. David Wiles takes a broad-based view of theatrical activity as something that occurs in churches, streets, pubs and galleries as much as in buildings explicitly designed to be ëtheatresí. He traces a diverse set of continuities from Greece and Rome to the present, including many areas that do not figure in standard accounts of theatre history